CYBER WARFARE AND PHYSICAL CONFLICTS: EVIDENCE FROM THE RUSSIAN-UKRAINIAN CONFLICT (2022-2024) - Oliveira, João Marcos Barbosa; Barros, Carlos Henrique do Nascimento; Marques, Ismael Deus; Souza, Jovair Pazzini de Melo; Stefani, Eduardo (Seven Editora, 2025)
This article investigates the use of cyber warfare during the conflict between Russia and Ukraine (2022-2024), emphasizing its interaction with conventional military operations. Based on data from the European Repository of Cyber Incidents (EuRepoC), the correlation between the intensity of cyber attacks and physical combat, the occurrence of physical effects resulting from cyber actions and the temporality of incidents in relation to the phases of the conflict were analyzed. The results show that some cyber operations were coordinated with traditional military actions, contributing to significant impacts in the theater of operations. Finally, the findings are discussed in the light of the Brazilian Army’s Cyber Warfare doctrine, identifying potential ways of updating it. DOI: https://doi.org/10.56238/sevened2025.026-001